2005
DOI: 10.1080/00498250500230750
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies on the intramolecular acyl migration of β-1-O-acyl glucuronides: Application to the glucuronides of (R)- and (S)-ketoprofen, (R)- and (S)-hydroxy-ketoprofen metabolites, and tolmetin by1H-NMR spectroscopy

Abstract: Conjugation of carboxylate drugs with D-glucuronic acid is of considerable interest because of the inherent reactivity of the resulting beta-1-O-acyl glucuronides. These conjugates can degrade by spontaneous hydrolysis and internal acyl migration. beta-1-O-acyl glucuronides and their acyl migration products can also react covalently with macromolecules with potential toxicological consequences. The spontaneous degradation of the diastereoisomeric beta-1-O-acyl glucuronide metabolites of the racemic drug ketopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 24 publications
3
23
0
Order By: Relevance
“…After administration of racemic ibuprofen it has been reported that the drug excreted in human urine is largely in the (S)-form, due to chiral inversion in vivo. If both R-and S-ibuprofen glucuronides had been present in the sample (as a diastereoisomeric mixture) [14] a pair of doublets would have been observed for the anomeric proton resonances, since these are clearly resolvable although there is some overlap of the J-coupled multiplets as shown by previous work on the chemically-related flurbiprofen [16] and ketoprofen [17]. However, from the measurements made here, the resonance observed for the anomeric proton showed only a single doublet.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…After administration of racemic ibuprofen it has been reported that the drug excreted in human urine is largely in the (S)-form, due to chiral inversion in vivo. If both R-and S-ibuprofen glucuronides had been present in the sample (as a diastereoisomeric mixture) [14] a pair of doublets would have been observed for the anomeric proton resonances, since these are clearly resolvable although there is some overlap of the J-coupled multiplets as shown by previous work on the chemically-related flurbiprofen [16] and ketoprofen [17]. However, from the measurements made here, the resonance observed for the anomeric proton showed only a single doublet.…”
Section: Resultsmentioning
confidence: 87%
“…Nevertheless, even in the absence of a large database of drug glucuronide half-life data, the half-life of 3.5 h determined here for ibuprofen glucuronide can also be compared with the value of 0.44 h for tolmetin [17] a drug withdrawn from the market because of adverse side effects. The half-life for the degradation of the diastereopmeric ester glucuronides of ketoprofen, an arylpropionic acid NSAID currently on the market, have also been derived recently at 1.45 h for the S-isomer and 0.67 h for the R-isomer [17].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, of the two isomers, only sipoglitazar-G2 was detected in vivo. Such conversion is generally known with acyl glucuronides for which ␤-1-O-acyl glucuronide is irreversibly converted to the 2-Oisomer (Skordi et al, 2005). The rates of acyl migration depend on the …”
Section: Downloaded Frommentioning
confidence: 99%
“…Hence, this technique could be applied to rank-order compounds within a chemical series based on the reactivity of their respective acyl-glucuronide conjugates. NMR spectrometric methods have also been introduced to monitor the stability of acyl glucuronides and elucidate the structures of their degradation products (35)(36)(37). The former task is accomplished in part by analyzing the resonance signals associated with the anomeric proton of the O-1-acyl glucuronide as a function of time.…”
Section: In Vitro Bioactivation Studiesmentioning
confidence: 99%